Nigerian health workers' views concerning factors influencing paediatric adherence to anti-retroviral therapy - Valerie J. Ehlers; Robert J. Chiegil (AOSIS, 2011)
Few studies have focused on paediatric anti-retroviral therapy (ART) adherence in Nigeria, probably because of the ethical challenges involved in studying children. The study aimed to identify factors that influence paediatric ART adherence as perceived by health care workers providing ART services in two cities in Nigeria. Knowledge about such factors would be used to formulate recommendations for enhancing paediatric ART adherence in Nigeria, for facilitating the tasks of the health care workers and for enhancing the ART programme's effectiveness. An exploratory descriptive qualitative research design was used to identify and to describe health care workers' views in Kano and Lagos, Nigeria. Three focus group discussions were conducted at two clinics that provide free paediatric ARVs (antiretroviral drugs). The transcribed data were analysed by using the framework approach of data analysis. Health care providers perceived poverty, illiteracy, stigma, discrimination, inappropriate care approaches, and parental dynamics as factors that influence paediatric ART adherence. Paediatric ART adherence levels in Nigeria could be enhanced by emphasising paediatric ART adherence counselling and by adopting a comprehensive family centred care approach, by improving free paediatric ART services and by empowering parents and reducing stigma and discrimination. Opsomming Min studies het al op pediatriese anti-retrovirale behandeling (ARB) nakoming in Nigerië gefokus, wat moontlik toegeskryf kan word aan die etiese uitdagings betrokke by die bestudering van kinders. Die studie het gepoog om faktore te identifiseer wat pediatriese ARB nakoming kan beΪnvloed, soos waargeneem deur gesondheidsdienswerkers wat ARB dienste verskaf in twee stede in Nigerië. Kennis van sulke faktore sal aangewend word om aanbevelings te maak om die pediatriese ARB nakoming in Nigerië te verbeter, om die taak van die gesondheidsorgwerkers te vergemaklik en om die ARM (anti-retrovirale medisyne) program se doeltreffendheid te verbeter.'n Verkennende beskrywende kwalitatiewe navorsingsontwerp was benut ten einde gesondheidswerkers in Kano en Lagos, Nigerië, se standpunte te identifiseer en te beskryf. Drie fokusgroepbesprekings is gehou in twee klinieke wat gratis ARMs verskaf. Die getranskribeerde data is ontleed deur die raamwerkbenadering tot data analise te gebruik. Gesondheidsdienswerkers het waargeneem dat armoede en ongeletterdheid, stigma en diskriminasie, ontoepaslike sorgbenaderings en ouerlike dinamika, faktore was wat pediatriese ARB nakoming beĭnvloed het. Pediatriese ARB nakomingsvlakke in Nigerië kan verbeter word deur pediatriese ARB nakomingsberading te beklemtoon, deur die aanvaarding van 'n omvattende gesinsgesentreerde sorgbenadering wat gratis ARB dienste bied, deur die verbetering van ARB dienste, die bemagtiging van ouers en die vermindering van stigma en diskriminasie.